2016
DOI: 10.1021/acsami.6b07893
|View full text |Cite
|
Sign up to set email alerts
|

Three Gel States of Colloidal Composites Consisting of Polymer-Brush-Afforded Silica Particles and a Nematic Liquid Crystal with Distinct Viscoelastic and Optical Properties

Abstract: Colloidal composites consisting of polymer-brush-afforded silica particles (P-SiPs) and a nematic liquid crystal (LC) exhibited three gel states with distinct viscoelastic and/or optical properties depending on temperature: (1) opaque hard gel, (2) translucent hard gel, and (3) translucent soft gel. We demonstrated that the transitions of the optical property and the hardness of the gels were due to the phase transition of the LC matrix and the glass transition of the grafted polymers of P-SiPs, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Using this photochemical behavior, we have previously achieved dynamic control of the viscoelastic and optical properties of liquid-crystalline composite gels. [25][26][27] In this study, we report unusual photoresponses in the UCST of polymer solutions employing an azobenzene-doped liquid crystalline mixture as solvent. We employed 4-heptyl-4 0 -cyanobiphenyl (7CB) containing 5 mol% of an azobenzene derivative (azo-doped 7CB) as the solvent.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Using this photochemical behavior, we have previously achieved dynamic control of the viscoelastic and optical properties of liquid-crystalline composite gels. [25][26][27] In this study, we report unusual photoresponses in the UCST of polymer solutions employing an azobenzene-doped liquid crystalline mixture as solvent. We employed 4-heptyl-4 0 -cyanobiphenyl (7CB) containing 5 mol% of an azobenzene derivative (azo-doped 7CB) as the solvent.…”
Section: Introductionmentioning
confidence: 86%
“…This azo content was confirmed to be enough to induce a definite photoresponse in liquidcrystalline mixtures. 24,26,27 Solutions of poly(methyl methacrylate) (PMMA) and polystyrene (PS) using 7CB were previously reported to exhibit UCST-type phase behavior. 28 We investigated the photoinduced changes of UCST in the PMMA and PS solutions using the azo-doped 7CB in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For composites containing high content of nanoclay (High-C/G group), the gels showed the highest elastic modulus G ′ , but also rather higher FDI values than that of Low-C/G and Gelatin gels particularly at high solid contents. This suggested that the excessive amount of nanoclay phase in the composites can increase the viscoelastic feature of the colloidal gels [47,48].…”
Section: Viscoelasticity and Self-healing Behavior Of The Binary Coll...mentioning
confidence: 99%
“…Polymer dispersed liquid crystals (PDLCs) form a special class of composite materials made of a polymer matrix containing pores filled with a low molecular weight liquid crystal (LC), and as such, they are said to have a Swiss cheese morphology [1,2]. PDLCs have drawn a particular attention in the literature from both fundamental and applied points of view, for their importance in a realm of modern technologies, and interesting properties encompassing morphology, structure, thermodynamic, thermo mechanical and viscoelastic aspects [3][4][5][6][7][8][9][10]. They offer major advantages over materials with similar functionalities because of their high availability, and competitive costs.…”
Section: Introductionmentioning
confidence: 99%